Short-term prognosis of contemporary interventional therapy of ST-elevation myocardial infarction: Does gender matter? - Zimmermann, Stefan; Ruthrof, Susanne; Nowak, Kathrin; Alff, Anna; Klinghammer, Lutz; Schneider, Reinhard; Ludwig, Josef; Pfahlberg, Annette; Daniel, Werner; Flachskampf, Frank A. (Clinical Research in Cardiology, 2009)
Background: A higher mortality risk for women with acute ST-elevation myocardial infarction (STEMI) has been a common finding in the past, even after acute percutaneous coronary intervention (PCI). We set out to analyze whether there are gender differences in real-world contemporary treatment and outcomes of STEMI. Patients and methods: A retrospective analysis of all consecutive patients with STEMI and acute coronary angiography with the intention of performing a PCI at our center 6/1999-6/2006 was carried out (n = 566). Data were examined for gender-specific differences regarding patients' characteristics, referral patterns, timing of acute symptoms, angiographic findings, procedural details, and adverse events at 30 days after PCI. Results: Women (n = 161) were on average 8 years older than men (n = 405), had higher co-morbidity, were more often transported to the hospital by ambulance and presented less often to the emergency room on their own (4.2% vs. 12.6% in men, P = 0.02). The pre-hospital delay from symptom onset to admission was significantly longer for women (median 185 vs. 135 min, P < 0.02). There was no gender difference in time from admission to PCI (median 46 min vs. 48 min, P = 0.42). Both genders received PCI with similar frequency (88.8% vs. 92.4%, P = 0.19), with similar success rates (83.2% vs. 85.3%, P = 0.68). Thirty-day overall mortality for women was not significantly higher than for men (8.7% vs. 7.2%, P = 0.6). Re-infarction or stroke within 30 days were rare for both genders without gender-specific differences whereas bleeding necessitating blood replacement was significantly more frequent in women (16.8% vs. 5.9%, P < 0.001). In multivariate analysis, female gender was not independently associated with a higher risk of 30-day mortality (OR 0.964, P = 0.93). Conclusions: Women underwent PCI therapy for STEMI with the same frequency and the same angiographic success as men. Despite their more advanced age and the higher prevalence of co-morbidities, they did not have a significantly higher 30-day mortality rate than men. Female gender was not an independent risk factor of 30-day mortality. Longer pre-hospital delays before hospital admission in women indicate that awareness of risk from coronary artery disease should be further raised in women. © 2009 Springer-Verlag.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Gender differences; Outcomes; Primary coronary intervention; ST-elevation myocardial infarction